2003
DOI: 10.1556/amicr.50.2003.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Salt- and Nisin-Sensitivity of Pressure-Injured BioluminescentListeria Monocytogenes

Abstract: Suspensions of a bioluminescent (luxAB) transformant of Listeria monocytogenes in pH 7.0 phosphate buffer were pressurised and the effect of the pressure treatment was monitored by plate counting. When the bacteria were suspended in NaCl- and nisin-free buffer the number of colony forming units (CFU) decreased by 3 and 6 log cycles after 300 MPA for 10 and 30 min, respectively. Supplementing the plating medium with 5% NaCl did not influence the colony forming capacity of non-pressurised cells, however, CFU of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…1986; Smith and Archer 1988). Farkas et al. (2003) have previously shown that pressure‐injured L. monocytogenes showed increased salt sensitivity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1986; Smith and Archer 1988). Farkas et al. (2003) have previously shown that pressure‐injured L. monocytogenes showed increased salt sensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…(2003) have previously shown that pressure‐injured L. monocytogenes showed increased salt sensitivity. They found that supplementing brain heart infusion agar plates with 5% NaCl did not influence the recovery of nonpressurized cells but residual populations of treated cells were reduced by several log 10 cycles in case of NaCl containing plates (Farkas et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation